Aktualisasi Agama Sikh di Indonesia Melalui Media Online - Wiranto, Erham Budi (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2024)
This study aims to understand the efforts of the Sikh religion in Indonesia to actualize itself within the context of online media development. Although Sikh adherents are scattered across various locations, the study focuses on the activities of the Sikh community at the Guru Nanak Social Foundation, the most active Sikh community in utilizing online media, particularly through its YouTube channel, to maintain their identity and culture amidst Indonesia's religious diversity. The research employs a qualitative analysis method on the content produced by this community, including the *"Sikh Indonesia Podcast"* series. Data were collected by observing published video content and analyzing interviews and discussions with community members recorded in podcast formats.  The findings indicate that the Sikh community's use of online media serves to preserve tradition and a platform to introduce Sikh religion and culture to a broader audience. Digital content, such as podcasts, plays a crucial in educating the public about Sikh values, strengthening community identity, and facilitating social integration through involvement in social activities like *seva* (community service). This strategy has proven effective in bolstering the Sikh community's existence in Indonesia, expanding public understanding of the Sikh religion, and promoting tolerance within a diverse society.